2009
DOI: 10.5664/jcsm.27552
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyses of Hypnotics and Infections: Eszopiclone, Ramelteon, Zaleplon, and Zolpidem

Abstract: Recent meta-analyses raising concern about risks of hypnotics suggest a need for more clarification of these risks. Methods: Because of preliminary suggestions that eszopiclone causes infections, we studied US Food and Drug Administration files on the 4 most-recently approved hypnotics, combined with published studies, to compile the risk ratios of infections for groups randomly assigned to receive hypnotics versus those assigned to receive placebos in controlled trials. Parallel controlled clinical trials of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 23 publications
2
42
2
Order By: Relevance
“…13 In the community, meta-analysis of evidence from randomised controlled trials of commonly prescribed Z-drugs (zopiclone, zolpidem, ramelteon and zaleplon) found increased risk of infection with Zdrugs compared with placebo (risk ratio 1.44; 95%CI [1.25, 1.64]). 14 In a recent general population study, benzodiazepine use was associated with increased pneumonia risk (odds ratio (OR) 1.54; 95%CI [1.42, 1.67]). 15 On the other hand, a study in elderly patients did not find a statistically significant association between benzodiazepines and pneumonia (OR 1.08; 95%CI [0.84, 1.47]), although wide CIs were reported, which may partly be due to low numbers of patients exposed to benzodiazepines in this study.…”
Section: Introductionmentioning
confidence: 99%
“…13 In the community, meta-analysis of evidence from randomised controlled trials of commonly prescribed Z-drugs (zopiclone, zolpidem, ramelteon and zaleplon) found increased risk of infection with Zdrugs compared with placebo (risk ratio 1.44; 95%CI [1.25, 1.64]). 14 In a recent general population study, benzodiazepine use was associated with increased pneumonia risk (odds ratio (OR) 1.54; 95%CI [1.42, 1.67]). 15 On the other hand, a study in elderly patients did not find a statistically significant association between benzodiazepines and pneumonia (OR 1.08; 95%CI [0.84, 1.47]), although wide CIs were reported, which may partly be due to low numbers of patients exposed to benzodiazepines in this study.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Similar to benzodiazepine, zolpidem binds to benzodiazepine receptors, which have also been associated with immunity and inflammation; therefore, this interaction might further increase the risk of infection. 5,8,[11][12][13][14] Given that APN is an infectious disease, we can provide a plausible explanation for the correlation of zolpidem use with an increased risk of APN. On the other hand, zolpidem has a short elimination t 1/2 value (approximately 2.6 hours in women) 21,22 and produces inactive metabolites 4,6 and therefore does not exert accumulating effects with repeated administration.…”
Section: Discussionmentioning
confidence: 94%
“…In 1 meta-analysis, Joya et al reported an infection risk ratio of 1.99 (95%CI 1.21-3.26; P = .006) for zolpidem users but did not report APN risk data. 12 In a recent 3-year follow-up study, Huang et al reported that the proportion of pyelonephritis was higher among patients using zolpidem than among those not using zolpidem (0.36% vs 0.19%, P = .035). 11 However, these authors did not consider some risk factors associated with APN, such as pregnancy, renal transplant, HIV/AIDS, diabetes mellitus, nephrolithiasis, and urinary tract infection, and did not calculate odds ratios or hazard ratios of the pyelonephritis risk.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations